2022
DOI: 10.1038/s41467-022-28752-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating flash droughts induced by the joint influence of soil moisture depletion and atmospheric aridity

Abstract: The emergence of flash drought has attracted widespread attention due to its rapid onset. However, little is known about the recent evolution of flash droughts in terms of the speed of onset and the causes of such a rapid onset phase of flash droughts. Here, we present a comprehensive assessment of the onset development of flash droughts and the underlying mechanisms on a global scale. We find that 33.64−46.18% of flash droughts with 5-day onset of drying, and there is a significant increasing trend in the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 81 publications
6
64
0
3
Order By: Relevance
“…The results show that in summer soil moisture in southern China and the United States decreases rapidly, making these regions prone to flash drought risks. This is consistent with some recent observations and analyses, which have shown increasing trends of flash drought events in humid areas in China (Wang et al, 2016;Yuan et al, 2019;Qing et al, 2022).…”
Section: Timing Of Global Drought Occurrencesupporting
confidence: 93%
“…The results show that in summer soil moisture in southern China and the United States decreases rapidly, making these regions prone to flash drought risks. This is consistent with some recent observations and analyses, which have shown increasing trends of flash drought events in humid areas in China (Wang et al, 2016;Yuan et al, 2019;Qing et al, 2022).…”
Section: Timing Of Global Drought Occurrencesupporting
confidence: 93%
“…Drought stress is one of the most severe difficulties encountered by land plants; it disrupts plants’ metabolism, photosynthesis, and cell structure, thereby impairing plants’ productivity ( Pandey and Shukla, 2015 ; Chen et al., 2017 ; Qing et al., 2022 ). Recently, many studies have shown that NACs can upgrade the drought resistance of Arabidopsis, rice, wheat, and maize ( Tran et al., 2004 ; Hu et al., 2006 ; Huang et al., 2015 ; Zhu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The short‐period increasing LE flux and stable sensible heat flux were not found in areas with dry climates such as western North America (Figure 3c) which can be due to the limited SM, leaf evaporation, and transpiration there. Additionally, there was no close linkage between DSL and heatwave in monsoon regions due to the influence of ocean‐atmosphere teleconnections (Qing et al., 2022). Specifically, even if the precipitation deficit during a DSL leads to decreasing SM and evapotranspiration, once the monsoon starts, the atmospheric humidity level tends to increase, and then the warming process was disrupted (Mo & Lettenmaier, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The feedback between SM and air temperature during a DSL provides essential information for heatwave that follows the DSL. Furthermore, the temporal evolutions of DSLs and heatwaves provide a new angle for the understanding of the spatiotemporal variation of compound dry‐hot extremes (Alizadeh et al., 2020; Mukherjee & Mishra, 2021) and flash drought (Mo & Lettenmaier, 2016; Otkin et al., 2018; Qing et al., 2022).…”
Section: Discussionmentioning
confidence: 99%